Portfolio Selection by DEMATEL and Analytic Network Process - Farokh Barzideh; Mohamad taghi Taghvifard; Fatemeh Zamanian (مطالعات تجربی حسابداری مالی, 2012)
This article is seeking to provide a proper model for selecting portfolio. To do that, first we should studied literature to discover suitable criteria. Then we have used a questionnaire for determining criteria's relationships to rank them. Managers of mutual fund asked to answer this questionnaire. To determine these relationships, we used DEMATEL technique. After that, these criteria were ranked by using Analytic Network Process. Thus, 50 companies with more cash in market between1385-1389 were chosen to assess these criteria. These companies were ranked by TOPSIS and a portfolio selected with the top 30. Return of portfolio consist of 30 companies had compared with the average return of portfolio consist of 50 stock and was shown by Sharp Index that the proposed model can be useful for managers in their portfolio selection.